2022
DOI: 10.1136/bmjos-2021-100272
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis on reporting practices as a source of heterogeneity in in vitro cancer research

Abstract: ObjectivesHeterogeneity of results of exact same research experiments oppose a significant socioeconomic burden. Insufficient methodological reporting is likely to be one of the contributors to results heterogeneity; however, little knowledge on reporting habits of in vitro cancer research and their effects on results reproducibility is available. Exemplified by a commonly performed in vitro assay, we aim to fill this knowledge gap and to derive recommendations necessary for reproducible, robust and translatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…However, challenges in translating findings from in vitro research to the clinic may hinder efforts to replace animal research. Poor reporting of measures to reduce the risk of bias in in vitro studies may contribute to this translational challenge [ 2 ], and research which systematically identifies such issues [ 3 ] may lead to improvements in the design, conduct and reporting of in vitro research, and, thereby, their adoption as alternatives to animal research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, challenges in translating findings from in vitro research to the clinic may hinder efforts to replace animal research. Poor reporting of measures to reduce the risk of bias in in vitro studies may contribute to this translational challenge [ 2 ], and research which systematically identifies such issues [ 3 ] may lead to improvements in the design, conduct and reporting of in vitro research, and, thereby, their adoption as alternatives to animal research.…”
Section: Introductionmentioning
confidence: 99%
“…The application of systematic review methodologies to in vivo animal studies has, similarly, identified opportunities for improvement [ 6 , 7 ]. More recently, reviews of in vitro data have suggested similar problems may be prevalent there [ 2 , 3 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that in vitro studies are often not reported with sufficient transparency for readers to appraise their methodological rigour and interpret the results. Two recent systematic reviews of drug discovery studies using cancer cell lines highlight the scale of the issue [3,4]: the majority of papers analysed in these reviews lacked basic information about experimental procedures, such as the type of control used, how cell lines were identified, cell passage numbers or the concentration of key medium constituents. In one analysis, a quarter of the papers also lacked even the most rudimentary information on cell culture conditions, such as cell density, carbon dioxide concentration or temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Significant differences between the results of the studies analysed could not be explained based on the limited experimental information reported in the papers, which raises concerns about the reliability of these studies and their translational value. Most in vitro studies also lack information pertaining to the internal validity of the experiments, such as details about whether randomisation or blinding were used, the criteria used to exclude data, or how sample sizes were determined [4,5]. Without clarity on the experimental approach and statistical methods used, a reader cannot evaluate the extent to which bias may have influenced a study's results, whether the analysis is appropriate, or how generalisable the findings may be.…”
Section: Introductionmentioning
confidence: 99%
“…The application of systematic review methodologies to in vivo animal studies has, similarly, identified opportunities for improvement [5,6]. More recently, reviews of in vitro data have suggested similar problems may be prevalent there [2,7,8].…”
Section: Introductionmentioning
confidence: 99%